THE INFLUENCE OF EXCHANGEABILITY, LEVERAGE, INFLATION, AND INTEREST RATE ON FINANCIAL PROBLEMS AMONG MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE DURING 2018-2021 - Adiputra, I Gede; Ruslim, Herman (International Journal of Application on Economics and Business, 2023)
Many companies are facing financial difficulties and some are failed into bankruptcy. One of the categories of financial distress is business failure which is mostly caused by economic and financial factors. This research provides empirical evidence regarding internal and external factors that affect the financial distress of several companies. The sample consists of 25 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2021. This study used multinomial logit regression analysis with liquidity and leverage as internal variable factors, inflation, and interest rates as external variable factors of the companies. The data had used secondary data derived from financial statements. The results showed that Exchangeability and Leverage had significant effects on Financial Distress meanwhile Interest Rates and Inflation had not influenced the Financial Distress significantly.”